May E-Governance Create Digital Divide? - Romke, Rowshon Ara (Asian Business Review, 2013)
Developing country (DC) governments have been using information and Communication technologies (ICTs) supporting and transforming the external Workings of governance by processing and communicating data. E-Governance should be seen to encompass all ICTs, but the key innovation is computer networks. Bangladesh has failed to progress towards achieving its target as envisaged in its information Technology (IT) policy documentation. Besides, the unequal access to computers and other digital technologies in the developing world from the developed world creates digital divide. Closing the technology gap would lift people out of poverty, while creating a large business opportunity for the high technology industry (World Resources Institute, 2000). My aim in this paper is to present an outline of E-Governance which create digital divide in Bangladesh. This type of research is rare and it would help the society and the country to understand the problem of digital divide and the progress of E-Governance. The paper concludes some problems designed to stimulate farther thoughts and advanced research. JEL Classification Code:  G39
Keywords: E-Governance; Digital Divide; Digitally Wealthy; Digitally Poor